Systemic treatment and liver transplantation for hepatocellular carcinoma: two ends of the therapeutic spectrum - Burroughs, Andrew; Hochhauser, Daniel; Meyer, Tim (The lancet oncology, 2004)
Hepatocellular carcinoma is the fifth most common malignant disorder and causes nearly 1 million deaths a year worldwide. A background of cirrhosis is the major risk factor, and in Asia and subSaharan Africa, cirrhosis is attributable mainly to endemic hepatitis B infection. In Europe and the USA the incidence of hepatocellular carcinoma is increasing as a result of the high prevalence of hepatitis C. The only curative treatments are surgical resection or liver transplantation, but only a few patients are eligible for these procedures. Local ablative treatments such as ethanol injection can lengthen survival in selected patients, and radiofrequency ablation also shows promise. Unfortunately, most patients are suitable only for palliative treatment because of the extent of their tumour or background liver disease or both. For these patients, a wide range of therapeutic interventions have been assessed, including transarterial embolisation (with or without chemotherapy), hormone therapy with antioestrogens and androgens, octreotide, interferon, and both arterial and systemic chemotherapy, of which only chemoembolisation improves survival over symptomatic care. Tamoxifen is ineffective, and there are insufficient randomised data to show the benefit of any other intervention. In this review, we focus on two ends of the therapeutic spectrum—transplantation, which is highly effective but applicable to only a few patients, and systemic chemotherapy, which is of uncertain benefit but widely applicable.